Analisis Penilaian Kesehatan KSPPS BMT di Kecamatan Bungus Teluk Kabung Pada Masa Pandemi Covid 19 - Dewi Sartika; Fitrah Mulyani; Andre Ilyas (Universitas Dharma Andalas, 2021)
The purpose of this research was to determine the Health Level of the KSPPS BMT in Bungus Teluk Kabung District during the Covid 19 pandemic by referring to the Regulation of the Deputy for Supervision of the Ministry of Cooperatives and Small and Medium Enterprises of the Republic of Indonesia No. 07/Per/Dep.6/IV/2016. This research is included in the types of quantitative and qualitative research. In accordance with the objectives to be achieved in this research, namely to reveal the health condition of the KSPPS BMT in Bungus Teluk Kabung Subdistrict during the Covid 19 Pandemic. The data collection methods used in this research are field research and library research. The method of data analysis in this research uses capital ratios, quality of productive assets, management, efficiency, liquidity, independence and growth, cooperative identity and compliance with Sharia principles. The results of the health assessment that has been carried out by the KSPPS BMT in Bungus Teluk Kabung Subdistrict, the results of the health level of the KSPPS BMT Bungus Barat are